1993
DOI: 10.1063/1.464921
|View full text |Cite
|
Sign up to set email alerts
|

Highly vibrationally excited HCN/HNC: Eigenvalues, wave functions, and stimulated emission pumping spectra

Abstract: Articles you may be interested inAb initio calculation of a global potential, vibrational energies, and wave functions for HCN/HNC, and a simulation of the A-X̃ emission spectrum J. Chem. Phys. 99, 308 (1993); 10.1063/1.465809 Highly excited vibration-rotation states of floppy triatomic molecules by a localized representation method: The HCN/HNC molecule J. Chem. Phys. 93, 3039 (1990); 10.1063/1.458838 The extraction of dynamics and the classical mechanical simulation of low resolution regular and chaotic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…2,[22][23][24][25][26][27] There are two major ingredients in a quantum investigation of highly excited vibrational dynamics, namely an accurate global PES and efficient solution of the vibrational eigenequation. Much effort has been devoted in this case to the development a global PES that is capable of describing both isomers as well as the isomerization barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[22][23][24][25][26][27] There are two major ingredients in a quantum investigation of highly excited vibrational dynamics, namely an accurate global PES and efficient solution of the vibrational eigenequation. Much effort has been devoted in this case to the development a global PES that is capable of describing both isomers as well as the isomerization barrier.…”
Section: Introductionmentioning
confidence: 99%
“…2,24,[39][40][41][42] However, all previous studies were based on empirical PESs of some form for theà 1 A state and imposed the Condon approximation that assumes a constant transition dipole. These approximations lead to uncertainties that are not readily interpretable.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Bentley et al carried out an ab initio calculation on the spectrum of highly vibrationally excited HCN/HNC. 2 They calculated eigenvalues, wave functions, and theoretical SEP spectra. Their calculation showed that the wave functions of levels which are located near or above the isomerization barrier, such as ͑0,4,4͒ or ͑5,10,0͒, are localized in the HCN well.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have considered only stabilized metastable HO 2 molecules and a constant density of states and hence avoided the unimolecular dissociation as well as the definition of the density of states. Accurate calculations of the rovibrational levels of HCN have been reported by several authors [39][40][41] using variational methods and different potential energy surfaces. Unfortunately, these calculations have been carried out only for low total angular momenta (J e 2) and energies up to ca.…”
Section: Dynamics Of the Reaction Ar + Hcn F Ar + H + Cnmentioning
confidence: 99%